Internalization of Qur’anic and Hadith Values through Wirid and Bakolah Traditions in Minangkabau Society: A Living Qur’an Approach - Dapit Amril; Hafizullah; Cecep Romli (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2026)
This study examines the process of internalizing Qur’anic and Hadith values through the wirid and bakolah traditions practiced by the male community in Jorong Pialai, Nagari Balimbing, Tanah Datar Regency. This tradition combines dimensions of religious ritual with the socio-cultural practices of the Minangkabau society rooted in the principle of “Adat basandi syarak, syarak basandi Kitabullah” (Customs based on Islamic law, Islamic law based on the Qur’an). The study employs a descriptive qualitative method with phenomenological and socio-anthropological approaches. Data were collected through participatory observation, in-depth interviews with twelve key informants, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that the internalization of Qur’anic and Hadith values occurs through three primary mechanisms: (1) habituation through the routine practice of wirid every Monday night, which forms the religious habitus of the congregation; (2) role modeling by religious leaders who serve as exemplars in worship devotion and noble character; and (3) bakolah or traditional oratory that conveys moral-religious messages through local language and cultural expressions. The internalized values encompass sincerity and spiritual tranquility, communal solidarity and Islamic brotherhood (ukhuwah Islamiyah), patience and virtuous character (akhlakul karimah), as well as the preservation of tradition and cultural identity. These findings reinforce the argument that local traditions can serve as effective media for vivifying Qur’anic teachings within the socio-cultural context of communities, provided such traditions are grounded in authentic Islamic values.